A survey on agents applications in healthcare: Opportunities, challenges and trends - Sulis, Emilio; Mariani, Stefano; Montagna, Sara (Computer methods and programs in biomedicine, 2023)
Background and Objective: The agent abstraction is a powerful one, developed decades ago to represent crucial aspects of artificial intelligence research. The meaning has transformed over the years and now there are different nuances across research communities. At its core, an agent is an autonomous computational entity capable of sensing, acting, and capturing interactions with other agents and its environment. This review examines how agent-based techniques have been implemented and evaluated in a specific and very important domain, i.e. healthcare research. Methods: We survey key areas of agent-based research in healthcare, e.g. individual and collective behaviours, communicable and non-communicable diseases, and social epidemiology. We propose a systematic search and critical review of relevant recent works, introduced by an exploratory network analysis. Results: Network analysis enables to devise out 5 main research clusters, the most active authors, and 4 main research topics. Conclusions: Our findings support discussion of some future directions for increasing the value of agent-based approaches in healthcare.